Integration approaches for overlapping protected areas in the Qinghai-Xizang Plateau, China - Ping Huang; Weihua Xu; Zhenhua Zang; Ao Du (Global Ecology and Conservation, 2024)
Overlapping protected areas, where the same land is designated as more than one type of protected area, is a widespread issue that complicates the management and effectiveness of the protected area network. Systematically assessing the extent of overlap, along with their effective integration, is crucial for enhancing the effectiveness of protected areas in meeting conservation objectives. We take the Qinghai- Xizang Plateau as a case study, conducting a quantitative assessment of the spatial relationships among six distinct categories of protected areas. We compare the efficacy of two scenarios aimed at integrating overlapping protected areas. Scenario 1 is based on the protection level and categories of protected area and Scenario 2 considers the conservation objectives in addition to Scenario 1. Our findings reveal that 240 (45.6%) protected areas on the Qinghai-Xizang Plateau experience overlap, encompassing about 6.6% of the total area of the protected areas. Notably, over 50% of geo-parks, scenic spots, and forest parks are affected by overlap. While both scenarios yielded comparable outcomes in terms of the overall number and area of integrated protected areas, they differed in their effectiveness across different categories. Compared to Scenario 1, Scenario 2 is more effective in 31 overlapping protected areas that match the conservation objectives. This study offers valuable insights and a reference for China and other nations grappling with the challenges of overlapping protected area designations, which will ultimately improve the efficiency of the protected area network.